Relationship of Knowledge, Age and Parity with the Selection of IUD Contraception in Lubuk Batang Lama Village Working Area UPTD Lubuk Batang Health Center, Oku Regency 2021 - Vera Anggraini; Rohaya Rohaya; Rizki Amalia (Science Midwifery, 2022)
Background: Contraceptive IUD is a contraceptive device that is inserted into the uterus, made of materials such as plastic, some are wrapped in copper, 3 and have various shapes. The spiral form is a form of IUD contraception that is widely known and known to the general public. Research Objectives: To determine the relationship between knowledge, age and parity simultaneously with the selection of the Intra Uterine Device (IUD) in Lubuk Batang Lama Village, Lubuk Batang Lama Village, Lubuk Batang Public Health Center, Ogan Komering Ulu Regency in 2021. Methods: Analytical Survey with Cross Sectional Design. This study uses primary data with a sample of 77 respondents. Research Results: Based on univariate analysis, 60 respondents (77.9%) chose IUD Contraception and 17 respondents (22.1%). 60 people (77.9%) lack knowledge and 17 people (22.1%). There are 23 people who are not at risk (29.9%) and 57 people who are at risk (70.1%). Low parity as many as 45 people (58.4%) and high parity as many as 32 people (41.6%). From the results of the bivariate analysis, it was found that there was a significant relationship between knowledge and the choice of IUD contraception with p value = 0.000, there was a significant relationship between age and the choice of IUD contraception with p value = 0.040, there was a significant relationship between parity and the choice of IUD contraception with p value = 0.047. Conclusion: There is a relationship between knowledge, age and parity with the selection of the Intra Uterine Device (IUD) in Lubuk Batang Lama Village, Lubuk Batang Lama UPTD Working Area of Lubuk Batang Health Center, Ogan Komering Ulu Regency in 2021. Suggestion: It is hoped that health workers can improve health services at the puskesmas in motivating candidates family planning acceptors, especially IUD contraception.